Understanding the earth (Cambridge university press, 1992)
Some of the foremost authorities in earth sciences contributed to this volume, first published in 1992, to provide a highly accessible and stimulating account of the rapid evolution of knowledge about the processes that drive and shape the Earth. Well-illustrated and extremely readable accounts cover many aspects of the earth sciences that are often confined to the more esoteric literature - from magma generation in the Earth to the formation of sedimentary basins. From contributions on the Earth's interior and its dynamic evolution to investigations of the natural and human-driven disturbances to the environment, Understanding the Earth reflects the increasingly integrated and multi-disciplinary research that has fed our understanding of the Earth's origin and its internal and surface processes, and provides an indispensable guide to students of modern earth sciences.